2008
DOI: 10.1007/s00464-008-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and open reversal of Hartmann’s procedure—a comparative retrospective analysis

Abstract: Laparoscopic reversal of Hartmann's procedure is a safe and practical alternative to open reversal. It can be performed with similar operative time, fewer complications, and a faster recovery time. Conversion during the reversal procedure was significantly impacted by severity of adhesions and marking of the rectal stump.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
3
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 25 publications
12
82
3
9
Order By: Relevance
“…Additionally, laparoscopic stoma reversal may help decrease the incidence of SSI. 19 Interval hernia repair as opposed to concomitant incisional hernia repair with stoma takedown may be warranted. Our data demonstrated no effect on SSI with skin closure; however, other studies 4 have suggested that the technique used to close incisions may affect the incidence of SSI.…”
Section: Commentmentioning
confidence: 99%
“…Additionally, laparoscopic stoma reversal may help decrease the incidence of SSI. 19 Interval hernia repair as opposed to concomitant incisional hernia repair with stoma takedown may be warranted. Our data demonstrated no effect on SSI with skin closure; however, other studies 4 have suggested that the technique used to close incisions may affect the incidence of SSI.…”
Section: Commentmentioning
confidence: 99%
“…Many authors report less intraoperative blood loss, shorter hospital stay, less wound infection rate, less postoperative pain [13,14]. The patient's convalescence, the first ambulation, and oral feeding are achieved faster [15].…”
Section: Operative Datamentioning
confidence: 99%
“…Laparoscopic reversal has shown less morbidity and mortality in relation to open Hartmann's reversal procedure. The morbidity with open Hartmann's reversal is reported at 4%-43% [13], and the mortality rate ranges from 4%-10% [15]. In Toro et al review, morbidity was 15.8% and the mortality was 0.7% [12].…”
Section: Operative Datamentioning
confidence: 99%
“…Использовали мето-дику введения первого порта справа в подвздошной или мезогастральной области, эндоскопического рассечения спаек в брюшной полости, мобилизации анастомозируемых сегментов толстой кишки. Лик-видацию стомы и наложение анастомоза выполняли последним этапом [11].…”
Section: материал и методыunclassified